The knowledge management role in transferring the Muslim heritage in golden age as a foundation of modern world: a literature review of “Bayt El Hikmah (The House Of Wisdom)” - Mohamed Mahmoud, Fatimetou Zahra; Mohamed Mahmoud, Ahmed; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2015)
Nowadays, many organisations are moving toward considering knowledge management as an essential part to help in working and achieving the organisation goal and to ensure its sustainability and development. It’s because they understand that the tangible assets are not the only valuable asset but also all the intangible assets should be managed to improve the organisation performance. From another point nowadays many people all over the world did not know about the rich Islamic heritage which was the foundation of our modern world. From this context we can see how the house of wisdom which was a great scientific academy and a library which include scholars from all the world and from different religions under the management of Muslims Caliph and their vision for creation, innovation and motivated all people to create and invent and he support them by the necessary technologies and suitable environment. Thus, the concept of knowledge management and principles was applied in house of wisdom since thousands of years and it has proven its success and it helped to raise and support the original inventions and to transfer it from a generation to another. This paper, represent a solution to the universities and especially the Islamic universities to promote their rankings and optimizing their state, by the merge between the Islamic heritage and knowledge management to result a successful organisation such as Bayt el Hikmah and to build a new generations who are aware of the greatness of Islam and of muslin scientists and who have the mind set of innovation and sharing knowledge.